2017
DOI: 10.1007/s10815-017-0965-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphokinetic parameters from a time-lapse monitoring system cannot accurately predict the ploidy of embryos

Abstract: Morphokinetic parameters subjected to investigation in the present study failed to improve the chance of selecting euploid embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…Multivariate analysis in the Euploid-ET arm also revealed that the transfer of TQE was not associated with the CPR, which is in line with previous studies reporting only mild associations between embryo ploidy and morphology [25,26].…”
Section: Discussionsupporting
confidence: 88%
“…Multivariate analysis in the Euploid-ET arm also revealed that the transfer of TQE was not associated with the CPR, which is in line with previous studies reporting only mild associations between embryo ploidy and morphology [25,26].…”
Section: Discussionsupporting
confidence: 88%
“…According to our data, PBB has no impact on the morphokinetic variables tPNf, t2–t9, and tMor, including the critical time parameters t3 and t5. Likewise, further subdivision of PBB embryo into euploid and aneuploid embryos did not show any differences in the embryonal development, assuming that the genetic status of the embryo does not influence early embryonal development as already confirmed by authors like Zhang et al [ 36 ]. An interesting side effect of our study was the evaluation of laser beam influences on embryo development.…”
Section: Discussionsupporting
confidence: 70%
“…Subsequently, Campbell’s aneuploidy risk model was applied by others on their own data sets, in order to test its ability to distinguish embryos on the basis of their ploidy. 30 , 42 , 43 Kramer and colleagues 42 retrospectively analyzed the morphokinetic development of 149 blastocysts obtained by means of either IVF or ICSI and biopsied in day-5 or day-6 cultures. The proposed model, however, failed to discriminate aneuploid embryos: the timing of blastocele formation and blastocyst expansion differed significantly from the predicted values.…”
Section: Algorithmsmentioning
confidence: 99%
“…In recent years, an increasing number of studies reported how the embryo’s morphokinetic development can be influenced by many confounding factors related to patient’s features or clinical and biological procedures. 2 , 27 30 , 37 43 …”
Section: Confounding Factorsmentioning
confidence: 99%
See 1 more Smart Citation